Cover Image. Issue 11 (27th October 2017) - Tordesillas, L.; Cubells‐Baeza, N.; Gómez‐Casado, C.; Berin, C.; Esteban, V.; Barcik, W.; O'Mahony, L.; Ramirez, C.; Pacios, L. F.; Garrido‐Arandia, M.; Díaz‐Perales, A.
Abstract : The cover image, by L. Tordesillas et al., is based on the Original Article Mechanisms underlying induction of allergic sensitization by Pru p 3, DOI:10.1111/cea.12962 .